The Exchange Rate in a Model with Heterogeneous Agents and Transactions Costs - Paul De Grauwe; Marianna Grimaldi (Center for Economic Studies and ifo Institute (CESifo), 2002)
In this paper we develop a model of the exchange rate. The existence of transactions costs introduces an important non-linearity. Agents have different beliefs about the future exchange rate. We show that this simple model creates great complexity in the market which is characterised by the fact that the exchange rate is disconnected from its fundamental most of the time. Periods of tranquility and turbulence alternate in unpredictable manner. Finally we show that this model mimicks most of the empirical puzzles uncovered in the literature.
Keywords: 330